Doctoral Dissertations in Economics: One-Hundred-Third Annual List (Journal of Economic Literature, 2006)
The list below specifies doctoral degrees conferred by U.S. and Canadian universities during academic year July 2005 to June 2006. Lists of degree recipients and subject classifications are provided by the university. Note: Dissertations without classifications may be found under “Y Miscellaneous Categories.”